Long term outcomes of the Humeral Intracondylar Repair System for management of canine humeral intracondylar fissures and humeral condylar fractures - Hood, Rebecca S.; Walton, Myles Ben; Innes, John F. (Frontiers in Veterinary Science, 2024)
Objective: To document long-term client-reported clinical outcomes and complications for the Humeral Intracondylar Repair System (HIRS) for treatment of humeral intracondylar fissures (HIF) and humeral condylar fractures (HCF) in dogs. Method: Data collection involved the review of clinical records and analysis of an owner questionnaire regarding complication occurrence and client-reported outcome. The 'Liverpool Osteoarthritis in Dogs' (LOAD) instrument was incorporated into the questionnaire. Results: 26 cases of HIF and 14 cases of HCF were included in the study, with follow-up times of over 12 months (range 13 to 97 months). 37 out of 40 cases reached long-term follow up: 25 out of 26 HIF cases, 11 out of 11 lateral condylar fracture cases and 1 out of 3 dicondylar fracture cases. Two cases of HIF suffered a gradual return of lameness in the long term; both dogs had concomitant medial coronoid disease. No other complications were reported in the long term. Excluding cases with concurrent issues affecting exercise, the median LOAD score at follow-up was 4 and 5 (out of 52) for HIF and HCF cases respectively. At long-term follow-up, 36 out of 37 cases were reported to have regained 'full function of the limb'. Clinical Significance: The results of this study, together with previously reported short and medium-term outcomes, support the use of HIRS for management of humeral intracondylar fissures and humeral condylar fractures.